Non-destructive diagnostic of high voltage electrical systems : theoretical analysis and practical applications - Vedral, Josef, 1972- (River Publishers, 2022)
This book describes the methods of signal processing used in the non-destructive diagnostics of mechanical and electrical properties of high-voltage electrical machines. Traditional and less traditional methods are given, which allow measuring the mechanical and electrical properties of these machines in order to determine their technical condition, including a description of their measurement methods. Separate chapters are devoted to the causes and methods of measuring and evaluating partial discharges arising in the insulation systems of high-voltage electrical machines. The following chapters provide an overview of the test methods used in the non-disassembly diagnostics of high-voltage transformers, rotary machines, high-voltage cables, insulators, surge arresters and circuit breakers. The book is intended for students of technical universities and experts in the field of non-destructive diagnostics of high-voltage electrical machines. The book was reviewed by Ing. Ji¿₉©Ư Br©Łzdil, Ph.D. MBA, Head of the HV laboratory of ORGREZ in the Czech Republic.
Keywords: Electric machinery -- Testing.; High voltages.; Nondestructive testing.; elektronické knihy; electronic books